2021
DOI: 10.21203/rs.3.rs-132516/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Clinical Value and Potential Mechanism of MTFR2 in Lung Adenocarcinoma via Bioinformatics

Abstract: Background: Mitochondrial fission regulator 2 (MTFR2) was involved in the progression and development of various cancers. However, the relationship between MTFR2 with lung adenocarcinoma (LUAD) had not been reported. Herein, this study analyzed the clinical significance and potential mechanisms of MTFR2 in LUAD via bioinformatics tools.Results: We found that the level of MTFR2 was increased, and correlated with sex, age, smoking history, neoplasm staging, histological subtype and TP53 mutation status in LUAD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Its altered expression affected the proliferation and metastasis of breast cancer and inhibited epithelial mesenchymal transition. Other similar studies found that the high expression of MTFR2 was related to the clinicopathology, diagnosis and prognosis, and promot-ed the occurrence and cancer development through p53-dependent cell cycle, DNA replication, and homologous recombination in lung cancer [13]. Such findings may highlight the potential role of MTFR2 in ESCC as a novel therapeutic target for treatment.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Its altered expression affected the proliferation and metastasis of breast cancer and inhibited epithelial mesenchymal transition. Other similar studies found that the high expression of MTFR2 was related to the clinicopathology, diagnosis and prognosis, and promot-ed the occurrence and cancer development through p53-dependent cell cycle, DNA replication, and homologous recombination in lung cancer [13]. Such findings may highlight the potential role of MTFR2 in ESCC as a novel therapeutic target for treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Some previous studies found that the high expression of [11,12]. Currently, some studies have shown that MTFR2 is overexpressed in glioblastoma (GBM) and lung cancer, and this was correlated with sex, age, smoking history, cancer stage, histological subtype, and TP53 mutation status of lung cancer [9,13]. However, the role of MTFR2 expression in ESCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of CDK1 in lung cancer reduces chemosensitivity and is related to the lower survival rate of patients [33][34][35]. According to the literature, direct inhibition of CDK kinase activity is the basic strategy for developing effective cell cycle inhibitors [36]. Based on the results of this study, we speculate that CDK1 has excellent value in the survival and prognosis of lung cancer patients and may provide some possibilities for targeted drug delivery of lung cancer chemotherapy.…”
Section: Discussionmentioning
confidence: 61%